PENGARUH MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS CANVA TERHADAP HASIL BELAJAR SISWA PADA MATERI HAK DAN KEWAJIBAN KELAS IV UPTD SD NEGERI 122349 PEMATANGSIANTAR - Rorenta Desfrinaya Simbolon; Minar Trisnawati Lumbantobing; Maria Barus (STKIP Subang, 2026)
The low learning outcomes of elementary school students in Civics education are caused by the use of conventional and less engaging learning media. This study aims to analyze the effect of Canva-based animated video learning media on students’ learning outcomes in the topic of rights and obligations for fourth-grade students at UPTD SD Negeri 122349 Pematangsiantar. This research employed a quantitative approach with a pre-experimental method using a one group pretest-posttest design. The research subjects consisted of 26 students. Data were collected through learning outcome tests in the form of pretest and posttest, and analyzed using the N-Gain test and paired sample t-test. The results showed an increase in the mean score from 32.30 to 85.92. The hypothesis testing indicated that tcount > ttable (15.729 > 1.708) with a significance value of 0.000 < 0.05, indicating a significant effect of the use of Canva-based animated video learning media on students’ learning outcomes. Thus, this media is effective in improving elementary students’ Civics learning outcomes.